PENGARUH QUALITY OF WORK LIFE DAN KESEJAHTERAAN PSIKOLOGIS TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MODERASI RESISTANCE TO CHANGE (STUDI PADA BIRO KEUANGAN SETDA PROVINSI JAWA TENGAH) - Agus Sehana, 1342020047 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was conducted to analyze (1) Is the effect of quality of work life on Organizational Citizenship Behavior? (2). What effects on the psychological well-being of Organizational Citizenship Behavior? (3). Is resistance to change moderating influence quality of work lifeÂ on Organizational Citizenship Behavior? (4). Is resistance to change moderating influence of psychological well-being on Organizational Citizenship Behavior?. Population and sample of this research are civil servants (PNS) Financial Bureau Secretariat of the Province of Central Java as many as 126 people. The sampling method used is the census sampling techniques. Census sampling is a sampling technique when all members of the population used as a sample. Technical analysis of the data used is quantitative descriptive analysis method, validity, reliability, multiple linear regression analysis. The type of data used are primary data and secondary data obtained through the study of documentation and questionnaires measurement using a scale linkert and be treated dolah in statistiik with SPSS 19.0 for Windows, the coefficient of determination (R2), F test and t test. From the analysis conducted this study concluded that:. (1) Quality of Work Life positive effect on Organizational Citizenship Behavior. This is evidenced by the level of significance probability variable Quality of Work LifeÂ of 0.000 <0.05 and t value of 6.629> t table 1,979. (2). Psychological wellbeing positive influence on Organizational Citizenship Behavior. This is evidenced by the level of significance probability Psychological Welfare variable of 0.000 <0.05 and t value of 6.835> t table 1,979. (3). Resistance to Change is not able to moderate the influence of Quality of Work LifeÂ on Organizational Citizenship Behavior. This is evidenced by the level of significance probability variable Resistance to Change at 0.099> 0.05 and t value of -1.664 <t table 1,979. (4). Resistance to Change may moderate the influence of Psychological Welfare on Organizational Citizenship Behavior. This is evidenced by the level of significance probability variable Resistance To Change 0.000 <0.05 and t value of 3.655> t table 1,979. Keywords: Quality of Work Life, Psychological Welfare, Resistance to Change and Organizational Citizenship Behavior.